2019
DOI: 10.3390/f10050393
|View full text |Cite
|
Sign up to set email alerts
|

De novo Characterization of the Platycladus orientalis Transcriptome and Analysis of Photosynthesis-Related Genes during Aging

Abstract: In China, Platycladus orientalis has a lifespan of thousands of years. The long lifespan of these trees may be relevant for the characterization of plant aging at the molecular level. However, the molecular mechanism of the aging process of P. orientalis is still unknown. To explore the relationship between age and growth of P. orientalis, we analyzed physiological changes during P. orientalis senescence. The malondialdehyde content was greater in 200-, 700-, and 1100-year-old ancient trees than in 20-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Our results indicate that the contents of MDA and H2O2 in leaves of C. oleifera increased with the increase of tree age, which was similar to other studies (Turfan et al 2020). However, the activity of SOD, POD, and CAT antioxidant enzymes in the ancient C. oleifera leaves was significantly higher, similar to the report of Chang et al (2019). Antioxidant enzymes are critical in the suppression of aging (Liu et al 2022), CAT and POD are specific enzymes that remove H2O2, and SOD mainly scavenges superoxide anion radicals.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our results indicate that the contents of MDA and H2O2 in leaves of C. oleifera increased with the increase of tree age, which was similar to other studies (Turfan et al 2020). However, the activity of SOD, POD, and CAT antioxidant enzymes in the ancient C. oleifera leaves was significantly higher, similar to the report of Chang et al (2019). Antioxidant enzymes are critical in the suppression of aging (Liu et al 2022), CAT and POD are specific enzymes that remove H2O2, and SOD mainly scavenges superoxide anion radicals.…”
Section: Discussionsupporting
confidence: 81%
“…These theories also indicate that tree senescence is formed under the combined action of many different factors. Meanwhile, due to different mechanisms and inducing factors of senescence (Chang et al 2019), different plants have inconsistent senescence processes. When encountering several external stress and internal senescence-related factors, some plants could form corresponding defense mechanisms through antioxidant enzymes, transcription factors, and signal transduction pathways to prolong their senescence process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on ancient P. orientalis have mainly focused on revealing its longevity mechanism [26,27] and mapping the climatically suitable habitat of P. orientalis for introduction and cultivation on a global scale [28,29]. Zhu et al [9,30] used nine SSR loci to analyze the genetic diversity of 94 300-year-old P. orientalis individuals growing near ancient temples or cemeteries in Beijing and confirmed that ancient P. orientalis played an important role in maintaining the genetic diversity and reproductive ability of the tree species.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [9,30] used nine SSR loci to analyze the genetic diversity of 94 300-year-old P. orientalis individuals growing near ancient temples or cemeteries in Beijing and confirmed that ancient P. orientalis played an important role in maintaining the genetic diversity and reproductive ability of the tree species. Chang et al [26] used the specific-locus amplified fragment (SLAF)-specific locus sequencing method to detect SNPs in the genomes of 100 individuals that were obtained from 13 ancient P. orientalis populations in China. The results suggested that the relationships among many individuals were inconsistent with their geographical locations.…”
Section: Introductionmentioning
confidence: 99%